ANALYSIS OF ACID MIXTURE COMPARISON ON THE PROCESS OF DESTRUCTION OF LEAD METAL (Pb) ON SAMPLE OF CARPET SHELL’S MEAT (Ruditapes variegatus) - Jola Latupeirissa; Nikmans Hattu; Semuel S. Pada; Vonny W. Soplanit (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2023)
ABSTRACT Analysis of the acid mixture ratio in the lead (Pb) metal deconstruction process in carpet shell’s meat samples (Ruditapes variegatus). In the deconstruction agent HNO3 : HCl (1:3), the average lead metal concentration contained in sweet clam meat is 4.6305 ± 1.066 mg/kg and for the HNO3 : H2SO4 (3:1), the average lead metal concentration contained in the same sweet clam meat was 5.6516 ± 2.556 mg/kg. Statistical test results showed no significant difference in the dissolving power of the acid mixture HNO3 : HCl (1:3) and HNO3 acid mixture: H2SO4 (3:1) as seen from the p>0.005 value, so both the HNO3 acid mixture: HCl (1:3) and HNO3 acid mixture: H2SO4 (3:1) can be used to deconstruct Pb metal in sweet clam meat (Ruditapes variegatus) because there is no significant difference in the two acid mixtures.